Analisis Proses Berpikir Kreatif Matematis Siswa SMP Kelas VII Pada Materi Bangun Datar - Hilmi, Yugi; Sri Mulyani, Fithri (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
The creative thinking process is a step taken to produce solutions to problem solving. This research is descriptive qualitative and the aim of the research is to analyze the creative thinking process of junior high school students based on Wallas Theory. The research subjects were 28 class VII students at SMPN 1 Mangunreja. Data collection techniques include creative thinking tests, conducting interviews and documentation. The results of the research are 1) students in the high creative thinking category are able to reach the stages of preparation, incubation, illumination and verification; 2) students in the creative thinking category are able to reach the preparation and incubation stages, while the illumination and verification stages still need to be developed; 3) students in the low creative thinking category are only able to reach the preparation stage so that the other three stages need to be developed. Keywords: creative thinking process, flat build